Pengaruh model STAD dan media papan pintar terhadap hasil belajar peserta didik kelas III sekolah dasar - Asyrof Dzakwan Rois; Fadhil Purnama Adi (Universitas Sebelas Maret, 2025)
This research investigates the influence of integrating the Student Teams Achievement Division (STAD) cooperative learning model with smart board media on the learning outcomes of third-grade students in Pancasila Education at SDN Tempel, Surakarta. Employing a quasi-experimental approach, the study involved both an experimental group and a control group. Data were collected using objective multiple-choice tests administered before and after the intervention. Findings revealed a significant improvement in the average learning outcomes of students who were taught using the STAD model supported by smart board technology compared to those in the control group (0.001 < 0.05). The experimental class demonstrated greater engagement, participation, and understanding of the subject matter. These results suggest that the implementation of STAD combined with smart board media is an effective strategy for enhancing student performance in Pancasila Education. Therefore, the integration of cooperative learning with digital media is recommended to improve cognitive learning outcomes and foster collaborative learning environments in elementary education settings.